Complex Sound’s Pitch and Tempo Perception: Psychological and Instructional Features - Kurapov, Anton; Balashevych, Aleksandra; Tsurikova, Hanna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The study investigates features of complex sound’s pitch and tempo perception depending on instructional set presence via the Likert scale and WAM test (wellbeing, activity, mood). Influence of objective complex sound characteristics (pitch and tempo) on a subjective evaluation of a music fragment, as well as the influence of instructional set (prior informing of a participant about objective differences between music fragments) on a subjective evaluation of a music fragment, were explored. The study looks at how people of different genders, whether they know how to play an instrument or have had musical education, perceive music. It was discovered that high pitch music was embraced as more fun, bright, light, and indecisive. Music with a higher tempo was also perceived as carefree, which is subjectively evaluated as less heavy and more fun. People with musical education background notice more differences between fragments with various pitches and tempos, specifically, they are capable of differentiating pitch and tempo changes better. In general, the study has shown that it is possible to manipulate objective characteristics of a complex sound in order to create widely acceptable subjective and psychological interpretation.